Potential Use of Phenolic Acids as Anti-Candida Agents: A Review - Teodoro, Guilherme R. [UNESP]; Ellepola, Kassapa; Seneviratne, Chaminda J.; Koga-Ito, Cristiane Y. [UNESP] (Frontiers Media Sa, 2015)
There has been a sharp rise in the occurrence of Candida infections and associated mortality over the last few years, due to the growing body of immunocompromised population. Limited number of currently available antifungal agents, undesirable side effects and toxicity, as well as emergence of resistant strains pose a considerable clinical challenge for the treatment of candidiasis. Therefore, molecules that derived from natural sources exhibiting considerable antifungal properties are a promising source for the development of novel anti-candidal therapy. Phenolic compounds isolated from natural sources possess antifungal properties of interest. Particularly, phenolic acids have shown promising in vitro and in vivo activity against Candida species. However, studies on their mechanism of action alone or in synergism with known antifungals are still scarce. This review attempts to discuss the potential use, proposed mechanisms of action and limitations of the phenolic acids in anti-candidal therapy.
Keywords: Candida; phenolic acids; phenolic compounds; antifungal effect; synergism